Software Development Dengan Extreme Programming (XP) Pada Aplikasi Deteksi Kemiripan Judul Skripsi Berbasis Android - Imam Ahmad; Rohmat Indra Borman; Jafar Fakhrurozi; Gavan Gorbi Caksana (Jurnal Inovtek Polbeng Seri Informatika, 2020)
To determine the topic or research title for the student's thesis, it is possible that the similarity of the title to the previous title, either accidentally or unintentionally. Therefore, the relevant section must check the titles submitted by students, so as to avoid plagiarism. The development of a thesis title similarity detection application is one of the efforts that can be made in solving this problem. The development of sosftware requires the right method to develop applications according to user needs. Extreme Programming (XP) is a part of the agile development approach based on iterative development, which is based on needs and solutions through collaboration among the development team. So, in this study, the development of a similarity detection application for the title of a thesis with the XP software development approach was carried out. Keywords - agile development, extreme programming, thesis